2014
DOI: 10.1103/physrevd.90.115028
|View full text |Cite
|
Sign up to set email alerts
|

Debye screening mass near deconfinement from holography

Abstract: In this paper the smallest thermal screening mass associated with the correlator of the CTodd operator, ∼ TrF µνF µν , is determined in strongly coupled non-Abelian gauge plasmas which are holographically dual to non-conformal, bottom-up Einstein+scalar gravity theories. These holographic models are constructed to describe the thermodynamical properties of SU (N c ) plasmas near deconfinement at large N c and we identify this thermal mass with the Debye screening mass m D . In this class of non-conformal model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(73 citation statements)
references
References 164 publications
(349 reference statements)
3
70
0
Order By: Relevance
“…The numerical procedure to solve the equations of motion for the metric and the scalar field is the one derived in [35] and used in the calculation of the Polyakov loop in [36,37], the heavy quark and light quark energy loss in [55][56][57], and the Debye screening mass in [58]. A reasonable fit to the lattice data for the speed of sound squared c 2 s = d log T /d log s in QCD (data from [30] and shown in Fig.…”
Section: Non-conformal Holographic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical procedure to solve the equations of motion for the metric and the scalar field is the one derived in [35] and used in the calculation of the Polyakov loop in [36,37], the heavy quark and light quark energy loss in [55][56][57], and the Debye screening mass in [58]. A reasonable fit to the lattice data for the speed of sound squared c 2 s = d log T /d log s in QCD (data from [30] and shown in Fig.…”
Section: Non-conformal Holographic Modelmentioning
confidence: 99%
“…This gives Tc = 150 MeV. For more details of the thermodynamics and other properties of this model parametrization see [58]. …”
Section: Non-conformal Holographic Modelmentioning
confidence: 99%
“…We emphasise that beyond the above items (i) and (ii) as some extreme cases further options are conceivable. For instance, T (z H ) may display a stationary or non-stationary inflection point, thus mimicking a second-order or sharp cross-over transition in the ambient thermalised medium [57][58][59]. Such cases are left for a separate study.…”
Section: Modifying the Blackness Functionmentioning
confidence: 99%
“…(This is actually not so surprising, as [20] has demonstrated that a two-parameter ansatz for the potential allows either for a cross-over, or a first-order phase transition or a second-order transition, depending on the choice of the parameters. Other examples can be found in [22,37], where one form of the bottom-up ansatz allows for different transition types.) To elucidate the origin of such a difference we exhibit in Fig.…”
Section: Adjusting a Dilaton Potentialmentioning
confidence: 99%
“…The approach belongs to a similar class of holographic models as the model class B in [22]: it has no confinement in the sense of [21] for t 1 +t 4 < √ 2/3 and no explicit fermionic degrees of freedom. Our ansatz is meant purely to match lattice QCD thermodynamics data in a restricted temperature interval.…”
Section: Adjusting a Dilaton Potentialmentioning
confidence: 99%